Primary Rhabdomyosarcoma of the Breast: Study of Three Cases at One Institution with a Review of Primary Breast Sarcomas - Junyoung Shin; Hee Jeong Kim; Dae-Yeon Kim; Gyungyub Gong; Kyung-Ja Cho (Korean Society of Pathologists & the Korean Society for Cytopathology, 2019)
Background Primary breast sarcoma (PBS) is rare, comprising approximately 1% of breast malignancies. Rhabdomyosarcoma (RMS) accounts for an extremely small proportion of PBSs, often leading to delayed histologic confirmation. Methods Upon reviewing Asan Medical Center's pathology database between 2000 and 2018, 41 PBS cases were retrieved, including three cases of primary RMS of the breast. Their clinicopathological features were analyzed, and the literature related to PBS and primary RMS of the breast was reviewed. Results We identified three primary breast RMS cases from our institution database, comprising 7.3% of PBS: one case each of spindle cell/sclerosing RMS (ssRMS), alveolar RMS (aRMS), and embryonal RMS (eRMS). All cases involved adolescents or young adults (14, 16, and 25 years, respectively) who underwent mastectomy or radiotherapy and were confirmed using immunohistochemical testing for myogenin, desmin, and myogenic differentiation. The ssRMS patient experienced recurrence at the operation site 4 months post-surgery despite undergoing concurrent chemoradiotherapy. The aRMS patient had multiple metastases at diagnosis and showed FAX3-FOXO1 fusion transcripts; she died 22 months after the diagnosis. The eRMS patient had enlarged axillary lymph nodes; post-radiotherapy, the lesion recurred as multiple metastases to the bone and lung. She died 18 months post-diagnosis. Conclusions Our experience on RMS cases suggests that spindle cell or small round cell malignancy in breasts of young female should raise suspicion for the possibility of primary or secondary RMS. To our knowledge, this is the second report of primary breast ssRMS and it may help clinicians who encounter this rare disease in the future.